2017
DOI: 10.1128/mcb.00442-16
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis Is Improved by Low Tumor Necrosis Factor Alpha Concentration through the Modulation of Gs-Coupled Receptor Signals

Abstract: In the early phase of bone damage, low concentrations of the cytokine tumor necrosis factor alpha (TNF-α) favor osteoblast differentiation. In contrast, chronic high doses of the same cytokine contribute to bone loss, demonstrating opposite effects depending on its concentration and on the time of exposure. In the bone microenvironment, TNF-α modulates the expression/function of different G protein-coupled receptors (GPCRs) and of their regulatory proteins, GPCR-regulated kinases (GRKs), thus dictating their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 60 publications
3
20
0
Order By: Relevance
“…The presence of TGF-β1 did not significantly affect the agonist potency (EC 50 = 10.0 ± 1.8 nM), even if the maximal effect of BAY in the production of cAMP was slightly increased ( E max = 4.3 pmol – TGF-β1; E max = 5.8 pmol + TGF-β1, P = 0.0565) even if it was not statistically significant. These results are in accordance with the effect of other cytokines on A 2B AR functionality ( Daniele et al, 2017 ); in fact, TNF-α has been demonstrated to increase A 2B AR coupling to the G s protein ( Daniele et al, 2017 ).…”
Section: Resultssupporting
confidence: 87%
“…The presence of TGF-β1 did not significantly affect the agonist potency (EC 50 = 10.0 ± 1.8 nM), even if the maximal effect of BAY in the production of cAMP was slightly increased ( E max = 4.3 pmol – TGF-β1; E max = 5.8 pmol + TGF-β1, P = 0.0565) even if it was not statistically significant. These results are in accordance with the effect of other cytokines on A 2B AR functionality ( Daniele et al, 2017 ); in fact, TNF-α has been demonstrated to increase A 2B AR coupling to the G s protein ( Daniele et al, 2017 ).…”
Section: Resultssupporting
confidence: 87%
“… 42 , 43 However, in our setting, we wanted to reproduce a low-grade chronic inflammatory condition and, hence, a low TNFα concentration was used. 44 , 45 Additional studies should be also carried on in order to evaluate the effects of NaBu on short-term TNFα-treatments in order to better investigate the effects of butyrate on the acute NF-κB activation. The study is also limited by the lack of the investigation of possible cytotoxic effects of NaBu which would be helpful in understanding the anti-proliferative action of this microbial derivative.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TNF- α also induces apoptosis in osteoblasts, as well as the production of other proinflammatory cytokines such as IL-1 β [ 32 , 33 ]. In contrast, some studies demonstrated that a low concentration of TNF- α can enhance and accelerate the differentiation of MSCs towards an osteoblast phenotype [ 34 ]. However, the mechanisms involved in bone remodeling and responsible for the “paradoxical effects” of TNF- α remain unclear [ 35 ].…”
Section: Discussionmentioning
confidence: 99%